People, power, and profits progressive capitalism for an age of discontent - Josephe E. Stiglitz (New York Norton & Company, 2019)
We all have the sense that our economy tilts toward big business, but as Joseph E. Stiglitz explains in People, Power and Profits, a few corporations have come to dominate entire sectors, contributing to skyrocketing inequality and slow growth. This is how the financial industry has managed to write its own regulations, tech companies have accumulated reams of personal data with little oversight, and government has negotiated trade deals that fail to represent the best interests of workers. Too many have made their wealth through exploitation of others rather than through wealth creation. If something isn't done, new technologies may make matters worse, increasing inequality and unemployment.
Includes bibliographical references (pages 257-352) and index.
Keywords: Wealth--Social aspects--United States